Acopladores direcionais de fibras ópticas com perfis de dispersão - Lima Júnior, Almir Wirth (2007)
We present a numerical investigation of the propagation and the switching of fundamental solitons in a two-core nonlinear fiber coupler constructed with Dispersion Profile Fiber (DPF). We have shown that appropriate shaping of the DPF profile is quite effective to recover, almost completely, the original switching behavior associated to the lossless situation. The study of soliton switching in DPF nonlinear fiber couplers provides possibilities for achieving, high efficiency in ultrafast all-optical signal processing, especially for optical switches and optical transistors. We initiate, studying the Maxwell Equations, the Coupled-Mode Equations, and the the Nonlinear Schrödinger Equation - NLSE, (analytic, and numerical approaches). After this, we detail the Propagation and Switching of "CW" and "Quasi-CW" Optical Signals in Optical Couplers, as well like we analyze, through theoretical form, the nonlinear double couplers of Dispersion Profiles Fibers (DPF). The last chapters explain the real objective of our Dissertation, or be, Detailed Analysis of the Optical Couplers of Profiles Dispersion Fiber (DPF), With, and Without Optical Losses, including two kinds of configuration (PA1 and PB1). We enclose the Dissertation with the Conclusions about the above referred studies